Sustainable learning for refugee children in South African primary schools: A theoretical approach - Adams-Ojugbele, Rasheedah O.; Hlalele, Dipane (AOSIS, 2021)
Background: The advent of democracy in South Africa brought about many changes in the education system. Policies and frameworks that guide the embracement of refugee children were formulated and later implemented. However, there are ongoing challenges experienced by this group and the incidents of poor access and quality of provision experienced by a larger population of refugee children, calls for urgent redress. Aim: This is a theoretical article that examines and analyses the education access, school integration and participation of refugee children. Setting: Focusing on refugee children in a primary school in South Africa. Method: Empirical study articles and reviews carried out on the education and resettlement of refugee children in their host countries between 2005 till date were randomly selected for inclusion in our analysis. Our intention was to understand how the education for refugees is generally conceptualised and the extent to which their lived experiences are captured. Result: Using Gibson’s theory of affordances as a lens, this article analyses the relationship between the new school environment and refugee children and evaluates the possibilities of sustainable learning for all. Conclusion: We argue for an expansive access, including social and academic support interventions that are balanced in terms of promoting the individual child’s abilities and needs for optimal development.
Keywords: Refugee children; Sustainable learning; School access; Social integration; School participation